KALIMAT TANYA DALAM NOVEL MURDER IN THE MEWS KARYA AGATHA CHRISTIE - TATARA, VALERIA ARIKA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
Abstract This study entitled Interrogative Sentence in the Novel Murder in The Mews by Agatha Christie is used to identify, classify and analyze the interrogative sentence found in the novel. The data have been collected from the dialogs among the characters found in the novel. The data then analyzed based on Aarts and Aarts concept (1982). In analyzing data the descriptive method is used. The result shows that interrogative sentence found in the novel are yes/no question, question tag, and wh-question. Three kinds of interrogative sentences found in the novel, there are also found . interrogative sentence without question word, one or two words followed by question mark in terms of its function in communication which can function as question. ─────────────────────────────────────────────────── Keywords: Interrogative sentence, grammatical analysis, novel Murder in the Mewsby Agatha Christie.